2015
DOI: 10.1073/pnas.1320611111
|View full text |Cite
|
Sign up to set email alerts
|

Single cell-derived clonal analysis of human glioblastoma links functional and genomic heterogeneity

Abstract: Glioblastoma (GBM) is a cancer comprised of morphologically, genetically, and phenotypically diverse cells. However, an understanding of the functional significance of intratumoral heterogeneity is lacking. We devised a method to isolate and functionally profile tumorigenic clones from patient glioblastoma samples. Individual clones demonstrated unique proliferation and differentiation abilities. Importantly, naïve patient tumors included clones that were temozolomide resistant, indicating that resistance to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
278
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(291 citation statements)
references
References 38 publications
6
278
2
5
Order By: Relevance
“…Heterogeneity of MGMT methylation within the tumor cell population has been reported as another source of variability of MGMT promoter methylation. One study observed the presence of both methylated and unmethylated clones in gliomaspheres derived from single cells of the same parental tumor by analyzing both protein expression and promoter methylation (34). Notably, neither MGMT methylation nor protein expression correlated with temozolomide resistance in this study.…”
Section: Discussionmentioning
confidence: 51%
“…Heterogeneity of MGMT methylation within the tumor cell population has been reported as another source of variability of MGMT promoter methylation. One study observed the presence of both methylated and unmethylated clones in gliomaspheres derived from single cells of the same parental tumor by analyzing both protein expression and promoter methylation (34). Notably, neither MGMT methylation nor protein expression correlated with temozolomide resistance in this study.…”
Section: Discussionmentioning
confidence: 51%
“…Furthermore, these investigators described an inverse correlation between stem signature and cell cycle gene expression, suggesting that the cells that form neurospheres in culture cycle more slowly compared with differentiated and differentiating tumor cells. A parallel, single-cell functional analysis of GBMs confirmed a strong variation of genomics and response to therapy (Meyer et al 2015). Additional detailed analysis of heterogeneity of this type will greatly expand our understanding of the differences between tumor cells both within and among GBM patients and improve the characterization of glioma CSCs.…”
Section: Genetics and Epigeneticsmentioning
confidence: 87%
“…Molecular heterogeneity exists even at the cellular level between cells that carry similar genetic alterations (50,51). Recently, single-cell transcriptional profiling of 430 cells from five different primary GBM tumors uncovered intratumoral heterogeneity at the cellular level.…”
Section: Complexity Of Tumor Heterogeneity In Gbmmentioning
confidence: 99%
“…Recurrence shows a high degree of variability tures for genes that regulate cell cycle, hypoxia, immune response, and stemness (50). Expanding single cells into clonal populations further demonstrated unique functionality including proliferation, differentiation abilities, and different sensitivities to temozolomide (51). The complexity of intercellular heterogeneity also relates to variations in epigenetic or transcriptional programs, which define a hierarchy of cells showing variable degrees of differentiation and stemness.…”
Section: The Process Of Tumor Recurrence In Gbmmentioning
confidence: 99%
See 1 more Smart Citation